ECONOMIA DA MONTANHEIRA , MULTIFUNCIONALIDADE DOS SISTEMAS E SUSTENTABILIDADE DOS MONTADOS - COELHO, INOCÊNCIO SEITA (PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes, 2010)
In this paper we demonstrate how important the economics of the Black Pig Alentejano race is in “montanheira” production system to the conservation of the cork oak and holm oak “montados”. We demonstrate also that the “montado” system is essential to assure the high quality and high prices of the goods provided by Black Pig extensive production system
The following values have no corresponding Zotero field: periodical: PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes pub-location: Zamora
Keywords: Alentejana Race Pigs; economics potential; environmental goods; high quality products; natural resources

A model for wildfire prevention planning in game resources - Zamora, R; Molina-Martínez, J R; Herrera, M.a.; Rodríguez y Silva, F (Ecological Modelling, 2010)
The high incidence of hunting activity and forest ﬁres in different ecosystems (particularly in Mediterranean ecosystems) requires a model, which allows for the comprehensive management of hunting resources and estimating the potential damage caused by this type of disturbance. This paper proposes a model for evaluating the socio-economic effects of forest ﬁres on hunting. Its cornerstone lies in evaluating hunting resource availability for each ecosystem within its territorial mosaic. Each game management unit (GMU) is identiﬁed by vegetation structure and habitat type. It presents a novel approach in which the economic value of each game management unit is linked to potential forest ﬁre damages. The effect a forest ﬁre has on an entire ecosystem depends on the intensity of its ﬂames. A sample study was undertaken in the province of Huelva in Andalusia (southern Spain). The socio-economic hunting vulnerability of the province of Huelva was 45,188,000D . The results obtained conﬁrmed the need for an economic appraisal of non-forest products in the forest and other woodland areas. Geographic Information System increases the ﬂexibility and simplicity of our methodology which permits immediate extrapolation to other agroforestry territories.
Keywords: fire severity; Fire-preventive planning; Hunting assessment; natural resources; Wildﬁre modeling

Analisis de los recursos de pastoreo aportados por el medio en dos Dehesas caracteristicas del sur de la provincia de Badajoz (España) - Sánchez, M Escribano; García, F Pulido (Archivos de zootecnia, 1994)
En este trabajo se analizan los recursos de pastoreo en dos explotaciones características de dehesa de Extremadura en el año 1992, Desde el punto de vista de la evaluación técnica, se observa que el sistema cubre, con recursos propios, entre el 54 y el 56 p.100 de las necesidades de la ganadería doméstica en el año de estudio, que se caracterizó por una climatología adversa, Por otro lado, los recursos de pastoreo suponen una de las principales utilidades económicas del sistema dehesa, cuya efectividad económica dependerá de la posibilidad de sustitución y del precio de mercado de las materias primas energéticas comerciales.
Keywords: agroforestry systems; Economic analysis; Extensive systems; natural resources; pastures